ASSESSMENT OF THE TRANSFER PHENOMENA FOR HEAVY METALS IN A FRESHWATER ECOSYSTEM: A FIELD STUDY - IONESCU, Petra; RADU, Violeta-Monica; MARCU, Ecaterina; CIOBOTARU, Irina-Elena; IVANOV, Alexandru Anton (Studia Universitatis Babeș-Bolyai Ambientum, 2016)
Increasingly higher concentrations of heavy metals in aquatic environments pose a major risk to living organisms, as a result of their bioaccumulation and toxicity. For the assessment of the bioaccumulation and trophic transfer, samples of water, sediments, aquatic plants (Ceratophyllum demersum, Potamogeton crispus and Spirogyra algae), molluscs (Viviparus viviparus) and fish (Ameiurus nebulosus and Scardinius erythrophthalmus) have been collected from Plumbuita Lake, located in a highly urbanized area of Bucharest city (Romania). After bringing the samples in solution, the following heavy metals have been determined using a spectrophotometer with atomic absorption - ContrAA 700 (Analytikjena): copper (Cu), chromium (Cr), cadmium (Cd), lead (Pb) and nickel (Ni). The distribution of heavy metals in the aqueous and solid phase for the collected samples has been assessed using their bioaccumulation factors in relation to water and sediments. For the molluscs species, metal determinations have been performed separately both for the soft tissue and for the shells, revealing that the soft tissue is more effective in accumulation of heavy metals compared to the shell.